Environmental calcium regulates gill remodeling in a euryhaline teleost fish. Issue 2 (25th July 2017) - Platek, Alexis; Turko, Andy J.; Donini, Andrew; Kelly, Scott; Wright, Patricia A.
GRAPHICAL ABSTRACT: Some fishes alter gill surface area by adjusting the height of the interlamellar cell mass in response to temperature, hypoxia, or salinity. We report that water hardness (Ca 2+ ) is another environmental factor that controls gill remodeling. Abstract: Some cyprindid and cyprinidontiform fishes undergo gill remodeling via the proliferation or regression of an interlamellar cell mass (ILCM), resulting in the modification of gill surface area in response to environmental hypoxia or ion levels. We hypothesized that ion‐related gill remodeling is regulated by water hardness through the interactions of Ca 2+ with tight junctions, predicting that gills will exhibit a lower ILCM and more surface area in a high Ca 2+ environment than in a low Ca 2+ environment. To test this hypothesis, we acclimated euryhaline mangrove rivulus ( Kryptolebias marmoratus ) to natural hard water ([Ca 2+ ] = 2.77 mmol/L), low Ca 2+ ([Ca 2+ ] = 0.13 mmol/L) freshwater, or high Ca 2+ water (5.88 mmol/L). Fish exposed to hard water had a significantly lower ILCM height than fish exposed to low Ca 2+ water. The addition of Ca 2+ to low Ca 2+ water restored gill surface area. Plasma Ca 2+ activity was not significantly different between groups. This study provides support for an influence of external Ca 2+ on gill remodeling and represents the first evidence of an ionic trigger (Ca 2+ ) for gill remodeling in teleost fishes.